Decisional Style, Sleepiness, and Online Responsiveness - Phillips, JG; Chow, YW; Ogeil, RP (Informa UK Limited, 2023)
As sleep problems can impair quality of work, an online questionnaire was used to examine relationships between sleepiness and decision making while obtaining unobtrusive indices of performance. Participants (N = 344) completed the Insomnia Severity Index, Epworth Sleepiness Scale, and the Melbourne Decision Making Questionnaire in a Qualtrics survey while reporting mobile phone use. Qualtrics recorded the time and the number of clicks required to complete each page of the survey. Multiple regression indicated that insomnia was associated with daytime sleepiness and Hypervigilance, and mobile phone use before bed. Participants with moderate sleepiness required a greater number of clicks to complete the questionnaire. Greater sleepiness was associated with longer times to complete these self-assessment tasks. Clinically significant sleepiness produces changes in performance that can be detected from online responsivity. As sleepy individuals can be appreciably and quantitatively slower in performing subjective self-assessment tasks, this argues for objective measures of sleepiness and automated interventions and the design of systems that allow better quality sleep. Practitioner summary: Work can require processing of electronic messages, but 24/7 accessibility increases workload, causes fatigue and potentially creates security risks. Although most studies use people’s self-reports, this study monitors time and clicks required to complete self-assessment rating scales. Sleepiness affected online responsivity, decreasing online accuracy and increasing response times and hypervigilance.
Keywords: Insomnia; errors; hypervigilance; lapses; mobile phone; sleepiness; 4203 Health Services and Systems; 42 Health Sciences; Sleep Research; Clinical Research; 1106 Human Movement and Sports Sciences; 1203 Design Practice and Management; 1701 Psychology; Human Factors; 4201 Allied health and rehabilitation science; 4207 Sports science and exercise; 5201 Applied and developmental psychology; Humans; Male; Female; Adult; Sleepiness; Surveys and Questionnaires; Decision Making; Middle Aged; Sleep Initiation and Maintenance Disorders; Young Adult; Internet; Self-Assessment; Adolescent; Humans; Sleep Initiation and Maintenance Disorders; Decision Making; Internet; Adolescent; Adult; Middle Aged; Female; Male; Young Adult; Self-Assessment; Surveys and Questionnaires; Sleepiness; Humans; Male; Female; Adult; Sleepiness; Surveys and Questionnaires; Decision Making; Middle Aged; Sleep Initiation and Maintenance Disorders; Young Adult; Internet; Self-Assessment; Adolescent